Preparation and Optical Property of Cadmium Molybdate Particles by a Solid-State Microwave Metathetic Route - Sung Lim, Chang (Asian Journal of Chemistry, 2012)
A solid-state metathetic (SSM) route assisted by microwave irradiation was used to synthesize cadmium molybdate (CdMoO4) particles under environmentally friendly conditions. Well crystallized CdMoO4 particles were formed at 600 ºC for 3 h, showing a fine and homogeneous morphology with sizes of 0.5-1.0 μm. The synthesized CdMoO4 particles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. The optical properties were investigated by photoluminescence emission and Raman spectroscopy.